The level of career indecision of senior high school students based on gender - Saputra, Edy Cahya; Purwanta, Edi; Astuti, Budi (International Journal of Evaluation and Research in Education (IJERE), 2025)
The purpose of this study was to determine the level of adolescent career indecision based on gender differences between male and female adolescents. This study used a quantitative descriptive method. The sampling technique employed a random sampling technique. The sample of this research was 361 students of class XII (12th grade) from 24 senior high schools in Kulon Progo Regency, Indonesia. The number of respondents based on gender consisted of 295 female and 66 male students. Data collection technique had been carried out using the career decision making difficulties questionnaire (CDDQ) in the 2022/2023 academic year through quantitative descriptive techniques and independent sample t-test. The independent sample t-test obtained the results of the Sig. less than 0.05 (0.031<0.05). Meanwhile, the results of descriptive analysis show that the level of career indecision of students who fall into the salient category is 26.44% of female students and 16.67% of male students. Thus, it can be concluded that there were respondents, both female and male students, who were included in the level of career indecision in the salient category or serious category that required assistance by a counselor to overcome its problem.